The sandfly fauna, anthropophily and the seasonal activities of Pintomyia spinicrassa (Diptera: Psychodidae: Phlebotominae) in a focus of cutaneous leishmaniasis in northeastern Colombia - Ovallos, Fredy Galvis (2013)
This study was conducted to identify the sandfly fauna and the anthropophilic species in a coffee-growing area of Villanueva, Norte de Santander, Colombia, a focus of American cutaneous leishmaniasis, and to analyse the relationship between the most frequent species and rainfall, relative humidity and temperature, with the aim of contributing to epidemiological surveillance in the area. Sandfly collections were performed fortnightly between February 2006-September 2007 using automatic light traps, Shannon traps, protected human bait and aspiration in resting places. A total of 7,051 sandflies belonging to 12 species were captured. Pintomyia spinicrassa (95.7%) predominated. Pintomyia oresbia and Lutzomyia sp. of Pichinde were found in the state of Norte de Santander for the first time. Pi. spinicrassa, Pintomyia nuneztovari, Micropygomyia venezuelensis, Lutzomyia (Helcocyrtomyia) scorzai and Lu. (Helcocyrtomyia) sp. were captured on the protected human bait. A significant association between Pi. spinicrassa abundance and the total rainfall and the average temperature and humidity 10 days before the collection was observed. The dominance of Pi. spinicrassa, a recognised vector of Leishmania braziliensis, especially during the dry periods, indicates that the risk of parasite transmission may increase.